The EFL Students’ 21st Century Skill Practices through E-Learning Activities - HADIYANTO HADIYANTO (Indonesian Research Journal in Education |IRJE|, 2019)
This study aimed to investigate students’ perception on 21st century skill practices through e-learning activities. The 21st century skills consist of two main components; soft skill and hard skills. Self-assessment questionnaires were distributed to 33 students to assess their practice level of their own 21st century skills in e-learning activities of TESOL Curriculum Design course. Students’ E-learning activities were designed and directed by a teacher in order to allow students practice the 21st century skills. The findings showed that the overall 21st century skills practiced by the students were at a high level. Looking at both components of 21st century skills, both soft skills and hard skills were practiced by students at a high level. All sub components of soft skill; communication skills, IT Skills, numeracy skills, problem solving skills and team work skills were practiced at a high level. However, IT skills were the highest among others skills practiced by the students in e-learning activities. Hard skills and their components; specific knowledge and specific skills of TESOL curriculum design were also practiced at a high level. The students attempted to gain their hard skills through practicing of soft skills in e-learning activities. In conclusion, the students were able to practice and enhance their 21st century skills through eLearning activities.